2015
DOI: 10.1016/j.jnucmat.2014.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopy characterization of the fission gas bubble superlattice in irradiated U–7 wt%Mo dispersion fuels

Abstract: Transmission electron microscopy characterization of irradiated U-7wt%Mo dispersion fuel were performed on various U-Mo fuel samples to understand the effect of irradiation parameters (fission density, fission rate, and temperature) on the self-organized fission-gas-bubble superlattice that forms in the irradiated U-Mo fuel. The bubble superlattice was seen to form a face centered cubic structure coherent with the host U-7wt%Mo body-centered cubic structure. At a fission density between 3.0 and 4.5×10 21 fiss/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…When they merge, a dislocation of gas bubbles inside the superlattice may form, which is marked by " " in Figure (6c-6d). Such dislocations also are observed in TEM images of gas bubble superlattices [2,4,6,80]. Therefore, we conclude that formation of gas bubble superlattices occurs through a nucleation and growth process.…”
Section: Effect Of Interstitial Mobility On Gas Bubble Structuresupporting
confidence: 63%
See 2 more Smart Citations
“…When they merge, a dislocation of gas bubbles inside the superlattice may form, which is marked by " " in Figure (6c-6d). Such dislocations also are observed in TEM images of gas bubble superlattices [2,4,6,80]. Therefore, we conclude that formation of gas bubble superlattices occurs through a nucleation and growth process.…”
Section: Effect Of Interstitial Mobility On Gas Bubble Structuresupporting
confidence: 63%
“…monolithic UMo fuels at different fission densities [1][2][3][4][5][6]. Descriptions of some observed gas bubble and grain microstructure features follow.…”
Section: Gas Bubble Structures Have Been Examined In Post-irradiationmentioning
confidence: 93%
See 1 more Smart Citation
“…on temperature at fission rate of 3.0×10 14 cm -3 s -1 (b) predicted by the rate theory models [17]. The experimental data were measured by Miao et al [48].…”
Section: Dislocation Density By Rate Theory Modelmentioning
confidence: 96%
“…In this form, in which U-Mo fuel particles are dispersed in an aluminum matrix, the build-up of a fuel-matrix-interaction (FMI) layer between the U-Mo fuel particle and the Al matrix limits the fuel performance. [19][20][21][22][23][24][25][26][27] In this study with energetic Xe irradiation [10] and other studies using alternate energetic ions, [28][29][30] it has been demonstrated that energetic ions also produce an FMI layer. A more complete description of the FMI result can be found in a related paper.…”
Section: U-mo Fuelsmentioning
confidence: 99%